2009
DOI: 10.1061/(asce)0733-9399(2009)135:2(85)
|View full text |Cite
|
Sign up to set email alerts
|

Random Lattice-Particle Simulation of Statistical Size Effect in Quasi-Brittle Structures Failing at Crack Initiation

Abstract: The modeling of statistical size effect of concrete structures that fail at crack initiation is studied, with special attention to the interaction between the autocorrelation length and the size of the failure zone. The mechanical failure of concrete is modeled by a network of axial springs with degrading stiffness. The heterogeneity of concrete is idealized by spatial variation of the tensile strength and fracture energy. As an example, the direct tensile test in plane stress, with the size range of 1:20, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…The geometrical randomness of discrete models is insufficient to simulate the size effect. To that end, one must include an autocorrelated random field of local strength, with the autocorrelation length equal to the RVE size (Carmeliet and de Borst 1995;Vořechovský and Sadílek 2008;Grassl and Bažant 2009).…”
Section: Review Of Weakest-link Model and Its Nonlocal Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometrical randomness of discrete models is insufficient to simulate the size effect. To that end, one must include an autocorrelated random field of local strength, with the autocorrelation length equal to the RVE size (Carmeliet and de Borst 1995;Vořechovský and Sadílek 2008;Grassl and Bažant 2009).…”
Section: Review Of Weakest-link Model and Its Nonlocal Extensionmentioning
confidence: 99%
“…Therefore, the RVE must be defined as the smallest volume whose failure causes the failure of the whole structure (Bažant and Pang 2007). Recently, the random particle model indicated that the RVE size is approximately equal to the autocorrelation length of the spatial variation of material strength (Grassl and Bažant 2009). Therefore, RVE strengths can be assumed to be mutually independent.…”
Section: Introductionmentioning
confidence: 99%
“…This is an experimentally challenging task, but can be tackled by increasingly realistic numerical models. For example, Van Mier et al [1,17] and Grassl et al [18,19] used discrete lattice model to study the size effect of quasi-brittle materials. Karihaloo et al [20] and Duan et al [6] used the fictitious crack model to investigate the size effect on concrete.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer and based on the theory of meso-mechanics, some outstanding researchers as Wrigers [65], Cusatis [66], Bazant [67,68] and Leite [69] established several models to study the problem with meso-mechanics theory and uniformization method. The results well disclosed that the initiation of crack is mostly from the interface between the aggregate and mortar, and the aggregate shape and grading as well as cement mortar strength affect a lot on the concrete strength.…”
Section: The Damage Mechanism Of Dam Concrete and Foundation Rockmentioning
confidence: 99%